Global Ecological Human Imprint, Sustainable Development and Environment: Assessment and Impacts - Shakir Hanna, Safwat H.; Harris, Kendal T.; Osborne-Lee, Irvin W.; Cesaretti, Gian Paolo; Misso, Rosa; Andreopoulou, Zacharoula S. (European Journal of Sustainable Development, 2014)
Ecological Human Imprint (EHI), sustainability, and environment form three points of the triangle of technology development. These three points when integrated are the key to understanding how to improve global sustainability. The present research focuses on assessment and impacts of global issues of sustainability of human activities. This research uses modeling of these points and predicts the impacts of human activities on our global Earth and its natural resources and in consequence, the economic and social impacts. Further, the model uses assessments to develop suggestions about how to conserve our global environment and natural resources for future generations. The model is constructed on data collected and analyzed using published data from USA Agencies: United Nation Agencies and other public published data from different countries in the world. Stella™ software is used in the development of the model to make the prediction for the next 100 years. The results of research applying the model are presented in three scenarios. These scenarios are formed applying (1) relaxed, (2) moderate, and (3) very conservative assumptions. In addition to these scenarios, predictions are developed according to the real-time data availability. According to the model, it is very important to maintain the trend of more efficient use of natural resources. Additionally, the more widespread education is very important to combat high demands for on natural resources and to conserve existing resources for continuation of global ecosystems and to supply life on Earth with the goods and services needed. Further, it is important to maintain the global the regenerative biological capacities (i.e. renewable resources) of Earth, while conserving (and developing new sources of) non-renewable resources. Finally, the model shows that the nations should close the gaps between population growth and the economic development. Key Words: Ecology, natural resources, world population, sustainable development